Involvement of the first transmembrane segment of human α(2)-adrenoceptors in the subtype-selective binding of chlorpromazine, spiperone and spiroxatrine - Laurila, JMM (Blackwell Publishing Ltd, 2011)
BACKGROUND AND PURPOSE: Some large antagonist ligands (ARC239, chlorpromazine, prazosin, spiperone, spiroxatrine) bind to the human α(2A)-adrenoceptor with 10- to 100-fold lower affinity than to the α(2B)- and α(2C)-adrenoceptor subtypes. Previous mutagenesis studies have not explained this subtype selectivity. EXPERIMENTAL APPROACH: The possible involvement of the extracellular amino terminus and transmembrane domain 1 (TM1) in subtype selectivity was elucidated with eight chimaeric receptors: six where TM1 and the N-terminus were exchanged between the α(2)-adrenoceptor subtypes and two where only TM1 was exchanged. Receptors were expressed in CHO cells and tested for ligand binding with nine chemically diverse antagonist ligands. For purposes of interpretation, molecular models of the three human α(2)-adrenoceptors were constructed based on the β(2)-adrenoceptor crystal structure. KEY RESULTS: The affinities of three antagonists (spiperone, spiroxatrine and chlorpromazine) were significantly improved by TM1 substitutions of the α(2A)-adrenoceptor, but reciprocal effects were not seen for chimaeric receptors based on α(2B)- and α(2C)-adrenoceptors. Molecular docking of these ligands suggested that binding occurs in the orthosteric ligand binding pocket. CONCLUSIONS AND IMPLICATIONS: TM1 is involved in determining the low affinity of some antagonist ligands at the human α(2A)-adrenoceptor. The exact mechanism is not known, but the position of TM1 at a large distance from the binding pocket indicates that TM1 does not participate in specific side-chain interactions with amino acids within the binding pocket of the receptor or with ligands bound therein. Instead, molecular models suggest that TM1 has indirect conformational effects related to the charge distribution or overall shape of the binding pocket.